Online Gaming Engagement and Adolescent Social Withdrawal: The Mediating Role of Family Cohesion - Kalogeropoulos, Dimitra; Papadopoulos, Eleni; Antoniou, Nikos (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to investigate the relationship between online gaming engagement and adolescent social withdrawal, with family cohesion examined as a mediating factor. Methods and Materials: A descriptive correlational design was employed with a sample of 388 adolescents in Greece, selected based on the Morgan and Krejcie sample size determination table. Standardized instruments measured online gaming engagement, social withdrawal, and family cohesion. Data analysis included Pearson correlation analysis using SPSS-27 to examine bivariate associations and Structural Equation Modeling (SEM) with AMOS-21 to test the hypothesized mediation model. Model fit was evaluated using χ², df, χ²/df, GFI, AGFI, CFI, TLI, and RMSEA indices. Findings: Pearson correlation results revealed that social withdrawal was positively correlated with online gaming engagement (r = .42, p < .001) and negatively correlated with family cohesion (r = -.36, p < .001). Online gaming engagement was also negatively correlated with family cohesion (r = -.28, p < .001). SEM demonstrated adequate model fit (χ² = 218.73, df = 94, χ²/df = 2.33, GFI = 0.93, AGFI = 0.90, CFI = 0.96, TLI = 0.95, RMSEA = 0.057). Path analysis showed that online gaming directly predicted higher social withdrawal (b = 0.41, β = 0.36, p < .001) and lower family cohesion (b = -0.29, β = -0.27, p < .001). Family cohesion negatively predicted social withdrawal (b = -0.39, β = -0.32, p < .001). Indirect effects confirmed partial mediation (b = 0.11, β = 0.09, p = .008), with a significant total effect of gaming on withdrawal (b = 0.52, β = 0.45, p < .001). Conclusion: The findings suggest that online gaming engagement contributes to adolescent social withdrawal both directly and indirectly through reduced family cohesion. Strengthening family cohesion may serve as a protective factor, mitigating the adverse psychosocial effects of excessive gaming.